The role of main microeconomic factors on the stock prices of selected Swiss companies - Tomáš Pražák (Financial Internet Quarterly, 2020)
This paper examines the role of main microeconomic factors on the stock prices of selected Swiss companies listed on the Six Swiss Exchange. Two basic theoretical approaches and interpretations of this relationship are frequently used. The efficient market hypothesis (Fama, 1970) assumes that stock prices already contain all the relevant information and the theory of arbitration (Ross, 1976, or Chen et al., 1986). The microeconomic factors are based on the financial situation in companies. Financial ratios, taken from the financial statements of the individual companies, are used for the analysis. In general, the study confirmed that profitability and debt ratios are the most important business factors from the prospective of impact on stock prices. The relationship between the observed variables is explored using panel regression analysis. The generalized method of moments for constructing a regression model is used. The sample period of the dataset is composed of annual data from 2006 to 2015.
Keywords: C58; D24; G21; 330; Financial ratios; panel regression; stock prices